Identification of construction quality parameters / Rafidah Ithnin - Ithnin, Rafidah (2006)
Quality is a must in every construction project, no matter size, types of projects, or complexity. It appears in two primary aspects of the project: in the value, serviceability, and appropriateness of all components, and in the processes that design and install them. If the process can be made uniform, efficient, repetitive, foreshortened, and, in short, better, through quality management efforts, the cost of the total project will be decreased. For the construction industry, implementing ISO 9001:2000 Quality Systems can complement and spur the industry towards adopting innovative and efficient construction technology and practices in order that projects can be completed within a stated period of time and with less wastage, giving adequate consideration to quality and safety requirement’s as well as giving due regard to the environmental and aesthetic aspects. The objectives of the study are to identify the construction quality parameters. In addition to this, it is also to determine the factors affecting the quality in construction industry with data collection by interview and questionnaires. The studies have been conducted in Pulau Pinang. All the parameters listed are influence the quality in construction work. Respondent agree that parameter A belongs to sufficient instruction and information in contract specification, drawing and design, and parameter D which is efficiency and effective planning and management by the owner, contractor and designer were the most factor influence the quality in construction industry. From the result it can be conclude that parameter A and D get the higher scale chosen by the respondent. ISO quality standard is not implement by all contractor in Malaysia were proven by data get through from returned questionnaire. The recommendation in order to improve quality in construction in Malaysia, is Malaysian contractor must certified with ISO quality standard where it encouraged Malaysian contractor venture abroad for construction project.